Experimental and numerical investigation on thermal performance of a quartz tube solid particle solar receiver. (1st September 2020) - Nie, Fuliang; Yu, Yupu; Bai, Fengwu; Wang, Zhifeng
Highlights: A quartz tube solid particle solar receiver (SPSR) was experimentally studied. The temperature increase in per unit irradiated length was higher than 630 K/m. Various factors affecting the thermal performance were investigated by a simplified numerical model. The importance of the influencing factors was compared by a sensitive analysis. Abstract: The thermal performance of a quartz tube solid particle solar receiver (SPSR) with the gravity driven packed particles moving down in a semi-annular particle flow channel has been experimentally and numerically investigated, and the particle flow channel in the quartz tube was shaped by a ceramic fiber insert. The SPSR was heated by a solar simulator with 7 Xenon lamps at 130A electric current which generated a mean irradiant flux of 276 kW/m 2 on the 0.26 m irradiated length, grey ceramsite sand with the solar weighted absorptivity of 72.34% was used in the study. The experimental results with a 6 mm particle layer thickness indicated the particle temperature increase of 164 K and the thermal efficiency of 50.25%. A thinner particle layer thickness was shown to improve the thermal performance of the SPSR as verified both in the experiments and simulations. Although the particle temperature increase in a single pass was not high enough in the experiments, compared with other types of SPSR, this design obtained an advantageous particle temperature increase in per unit irradiation length. Moreover, the particle temperature increase in a single pass can be promoted by a longer irradiated length, and therefore the requirement for continuous recirculation of the solid particles will be decreased which can greatly reduce the required parasitic power. Besides, according to the numerical model, the thermal efficiency can be further improved by various means such as improving the solar weighted absorptivity of the solid particles, reducing the particle layer thickness, increasing particle mass flow rate and so on. A sensitive analysis illustrated that the mean particle diameter had the minimal impact on the thermal performance among the various influencing factors, but a value of greater than 700 μm was recommended based on the simulation results.